Histological characteristics in Longissimus thoracis muscle of Italian and Polish crossbreed horse - Nicastro, Annarita; Corriero, Aldo; Nicastro, Francesco; De Marzo, Davide (Progress in Nutrition, 2016)
Owing to high cost, meat horse domestic production does not meet internal market demand, that is why such a livestock is mainly imported from Eastern Europe Countries. Fibre type composition deeply influences post-mortem changes in the conversion of muscle to meat, as well as the product quality. The aim of this study was to investigate histological characteristics of muscle fibres and adypocites related to two different horse genetic types (Abruzzese and Polish), sold in Italy. The two horse genetic types showed little variation in the fiber type of the meat, considering the least square means of all 3 fiber types (red, intermediate and white) found in the samples muscle. The alpha-white fibers were larger than beta-red and alpha-red (P